PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS BAAMBOOZLE MATERI LUAS DAN KELILING BANGUN DATAR DI KELAS V SEKOLAH DASAR - Rahmadani Rambe; Sartono; Yarisda Ningsih; Fadila Suciana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop valid, practical, and effective Baamboozle-based learning media for the Area and Perimeter of Flat Shapes material in grade V of Elementary School. The research design uses a mix method. The type of research is development research with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Baamboozle-based learning media was validated by material experts by 90, media experts by 95, and language experts by 93.33 with the category